Hole's human anatomy & physiology - Shier, David (McGraw-Hill Higher Education, 2004)
Hole's Human Anatomy and Physiology assumes no prior science knowledge and places emphasis on the fundamental concepts without overwhelming students with too much detail. The text supports main concepts with clinical applications, making them more relevant to students pursuing careers in the allied health field. The learning aids throughout the text, along with the reader-friendly writing style, create a highly-effective learning system for understanding the concepts of anatomy and physiology.